KONSTRUKSI TOKOH DALAM PEMBERITAAN DI MEDIA ONLINE(Analisis Framing Pemberitaan Mundurnya Ahok dari Partai Gerindra di media online) - Setiowati, Endang; Suciati, Pijar (Jurnal Vokasi Indonesia, 2019)
The resignation of Basuki Tjahaja Purnama (Ahok) from the Gerindra Party for opposing Gerindra's decision to support the bill on regional head elections (PILKADA) through the DPRD was no longer directly by the people, causing controversy among the people which also served as media for discussion. This study will look at how news framing from three online media, Liputan6.com Vivanews.com, and Metronews.com. The selection of these three online sites is based on media ownership. The substantive theory used to analyze is the theory of social construction of reality from Berger and Luckmann, and the theory of influence hierarchy from Shoemaker and Reese. The research method will use framing analysis from Robert N. Entman. The unit of analysis is reporting on the resignation of Ahok from the Gerindra Party on the three online news sites above when officially resigning on September 10 to September 17 2014. The result was that the three media were quite neutral in framing the case, although in the figure Ahok VivaNews looked more leads to negative, while Metronews is more positive. What is surprising is that Liputan6 gave so much attention to this issue, its advantages were Liputan6 raised from various angles and different sources.